An introduction to health planning in developing countries - Andrew Green (Oxford Univ, 1994)
This book covers all aspects of planning for health in developing countries. It emphasizes the many factors that impinge on health, the different non-governmental agencies involved in health activities, and the need for participation in planning by communities